New gold pincer-type complexes induce caspase-dependent apoptosis in human cancer cells in vitro - Zarić, Milan M.; Čanović, Petar P.; Stanojević Pirković, Marijana; Knežević, Sanja M.; Živković Zarić, Radica S.; Popovska Jovičić, Biljana; Hamzagić, Nedim; Simović Marković, Bojana; Marković, Nenad; Rilak Simović, Ana (Vojnosanitetski pregled, 2021)
Background/Aim. The use of cisplatin as a chemotherapeutic opened the door to the new metal-based drug research. New complexes containing metals such as platinum, palladium, ruthenium and gold have recently been analyzed as potential antitumor agents. The aim of the study was to investigate the cytotoxicity of Au(III) complexes with pincer-type ligands against cervical carcinoma cells (HeLa), breast cancer cells (MDA-MB-231 and 4T1) and colon carcinoma cells (HCT116 and CT26), as well as to examine the type and mechanism of cell death that these complexes induced in cancer cells. Methods. The cytotoxicity of Au(III) complexes was investigated by MTT assay. The apoptosis of the treated cancer cells was measured by flow cytometry and applying Annexin V/7AAD staining. The expressions of active proapoptotic protein Bax, antiapoptotic protein Bcl-2 and the percentage of cells containing cleaved caspase-3 in the treated cancer cells were determined by flow cytometry. Results. Complex 1 showed the most potent antitumor effect on HeLa cells, both compared to other two examined gold complexes and compared to cisplatin. The IC50 values on HeLa cells after 72 hours were 1.3 ± 0.4 μM, 3.4 ± 1.3 μM, 5.7 ± 0.6 μM, 26.7 ± 6.5 μM for complexes 1, 2, 3 and cisplatin, respectively. Complex 1 also exhibited the highest cytotoxicity against MDA-MB-231 and HCT116 cells compared to other tested compounds. The results of Annexin V/7AAD staining showed that all three gold complexes induced apoptosis in the treated cells. Our Au(III) complexes induced apoptosis by caspase-dependent mechanism, but we did not observe that the activation of an internal pathway of apoptosis occurred in the treated cancer cells. Conclusion. According to the results of our in vitro study, all three gold compounds, and especially complex 1, are promising candidates for a new generation of anticancer drugs.
Keywords: antineoplastic agents; apoptosis; caspases; enzyme assays; gold, compounds; neoplasms; toxicity, tests